Gardner's Syndrome-The Importance of Early Diagnosis: A Case Report and Review of Literature - Arati Chaudhary; P V Wanzari; Tushar Phulambrikar; Vanaja Reddy; Ashish Warhekar; Prashanthi Reddy; Shivakshi Khattri (Wolters Kluwer Medknow Publications, 2010)
Gardners syndrome (familial polyposis coli) is a genetic condition characterized by colonic polyps that carry a 100% risk of malignancy if untreated. Early diagnosis, in which an astute and knowledgeable dentist can play an essential role, is therefore of paramount importance. The presence of osteomas and multiple unerupted teeth provides the dentist with a major pointer to the possible presence of this disease, which may be provisionally diagnosed on the detection of other obvious features, like the cutaneous lesions. This fact is clearly illustrated by the accompanying case report of Gardners syndrome in a middle aged female patient who presented with the typical dental manifestations of the syndrome and timely detection of other manifestations halted the dreaded disease from further progression.